Interactions between particulate organic matter and dissolved organic matter in a weak dynamic bay revealed by stable isotopes and optical properties - Lu, Xuan; Wang, Chao; Lao, Qibin; Jin, Guangzhe; Chen, Fajin; Zhou, Xin; Chen, Chunqing (Frontiers in Marine Science, 2023)
Few studies have incorporated the tools of stable isotopes and optical properties to study the biogeochemical process of organic matter (OM), including particulate organic matter (POM) and dissolved organic matter (DOM), which prevents our comprehension of the interactions between POM and DOM in the marine environment. In this study, the origin, distribution, and fate of POM and DOM in Tieshangang Bay, a weak dynamic bay were investigated by measuring δ13C and δ15N of POM, dissolved organic carbon (DOC), and absorption and fluorescence of DOM (CDOM and FDOM). In the upper bay, POM source was mainly originated from terrestrial discharge, whereas the high fluorescence index (FI) indicated that external aquatic organism activity dominated DOM sources. In contrast, in the outer bay, the slightly increased δ13C and enriched δ15N of POM and enhanced fluorescence intensities of protein-like DOM components indicated the considerable contributions of the in situ biological activities to OM. A net addition of DOC and optical components of DOM occurred in both the upper and outer bays. The decomposition of terrestrial POM was responsible for the addition of DOM due to the weak dynamics in the upper bay, whereas the enhanced primary production and the strong decomposition of freshly produced POM jointly contributed to the addition of DOM in the outer bay. Our study suggests that hydrodynamics regulate the biogeochemistry and interactions of POM and DOM in the weak dynamic bay.